1990
DOI: 10.1002/clc.4960130611
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and anatomical considerations for safe and efficacious catheter ablation of arrhythmias

Abstract: Summary:The development of catheter ablation techniques for therapy of cardiac arrhythmias continues to evolve. Although many patients have benefited from catheter ablation procedures. failure to ablate the anhythmogcnic substrate and complications from the pulse used in these procedures remain too frequent occurrences. The pu'pose of this review is to focus on these problems of inefficacy and safety with attention directed to the role various direct current and radiofrequency pulses have had in the genesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Standard DC causes electrolysis on the metal electrode surfaces in the blood pool, thus producing micro bubbles containing the gaseous products of electrolysis. Arcing is another phenomenon that occurs when a critical electric current density between the electrode and surrounding blood is reached; the resulting flash or arc leads to a transient temperature rise up to a thousand within the bubble [69] . In 2011, Wittkampf et al [28] explored low-energy DC with a modified electrode configuration and reported the creation of myocardial lesions without arcing and only small gas bubbles that adhered to the metal electrode surface and disappeared within a few seconds.…”
Section: Limitations Associated With Ire Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard DC causes electrolysis on the metal electrode surfaces in the blood pool, thus producing micro bubbles containing the gaseous products of electrolysis. Arcing is another phenomenon that occurs when a critical electric current density between the electrode and surrounding blood is reached; the resulting flash or arc leads to a transient temperature rise up to a thousand within the bubble [69] . In 2011, Wittkampf et al [28] explored low-energy DC with a modified electrode configuration and reported the creation of myocardial lesions without arcing and only small gas bubbles that adhered to the metal electrode surface and disappeared within a few seconds.…”
Section: Limitations Associated With Ire Ablationmentioning
confidence: 99%
“…Arcing is another phenomenon that occurs when a critical electric current density between the electrode and surrounding blood is reached; the resulting flash or arc leads to a transient temperature rise up to a thousand within the bubble. [69] In 2011, Wittkampf et al [28] explored low-energy DC with a modified electrode configuration and reported the creation of myocardial lesions without arcing and only small gas bubbles that adhered to the metal electrode surface and disappeared within a few seconds. Furthermore, using a lowenergy PEF protocol, in 2019, Reddy et al [36] reported no arcing or significant visible bubble formation.…”
Section: Involuntary Muscle Contractionsmentioning
confidence: 99%